Britain and the Maastricht Negotiations - Forster, A. author. aut Link
IX, 211 p.
Keywords: This book examines the British government's negotiation of the Treaty on European Union which took place between December 1990 and December 1991. On the basis of documentary and interview based evidence of leading participants from Britain and Europe, it offers a unique insight into the objectives and motivations of the British government. It analyses the various constraints and pressures that impinged on the British government and sets its successes and failures in the Maastricht negotiations in a broader context of British European policy.